Dietary Exposure to Excess Saturated Fat During Early Life Alters Hippocampal Gene Expression and Increases Risk for Behavioral Disorders in Adulthood - Page, Kathleen C.; Anday, Endla K. (Frontiers in Neuroscience, 2020)
Purpose Maternal and postnatal diets result in long-term changes in offspring brain and behavior; however, the key mediators of these developmental changes are not well-defined. In this study, we investigated the impact of maternal and post-weaning high-fat diets on gene expression of key components mediating hippocampal synaptic efficacy. In addition, we evaluated the risk for impaired stress-coping and anxiety-like behaviors in adult offspring exposed to obesogenic diets during early life. Methods Dams were fed a control (C) or high-fat (HF) diet prior to mating, pregnancy, and lactation. Male offspring from control chow and high-fat fed dams were weaned to control chow or HF diets. The forced swim test (FST) and the elevated-plus maze (EPM) were used to detect stress-coping and anxiety-like behavior, respectively. Real-time RT-PCR and ELISA were used to analyze hippocampal expression of genes mediating synaptic function. Results Animals fed a HF diet post-weaning spent more time immobile in the FST. Swimming time was reduced in response to both maternal and post-weaning HF diets. Both maternal and post-weaning HF diets contributed to anxiety-like behavior in animals exposed to the EPM. Maternal and post-weaning HF diets were associated with a significant decrease in mRNA and protein expression for hippocampal GDNF, MAP2, SNAP25, and synaptophysin. Hippocampal mRNA expression of key serotonergic and glutamatergic receptors also exhibited differential responses to maternal and post-weaning HF diets. Hippocampal serotonergic receptor 5HT1A mRNA was reduced in response to both the maternal and post-weaning diet, whereas, 5HT2A receptor mRNA expression was increased in response to the maternal HF diet. The glutamate AMPA receptor subunit, GluA1, mRNA expression was significantly reduced in response to both diets, whereas no change was detected in GluA2 subunit mRNA expression. Conclusion These data demonstrate that the expression of genes mediating synaptic function are differentially affected by maternal and post-weaning high-fat diets. The post-weaning high-fat diet clearly disturbs both behavior and gene expression. In addition, although the transition to control diet at weaning partially compensates for the adverse effects of the maternal HF diet, the negative consequence of the maternal HF diet is exacerbated by continuing the high-fat diet post-weaning. We present evidence to support the claim that these dietary influences increase the risk for anxiety and impaired stress-coping abilities in adulthood.